EFEKTIVITAS FOTODEGRADASI P-KLOROFENOL DENGAN KATALIS TIO2 - Ana Hidayah Mukaromah (JURNAL LITBANG, 2005)
The effictiveness of p-chlorophenol photodegradation on catalyzed by TiO2 have been studied. The photo degradation process was carried out in closed reactor equipped with  UV lamp type-C. The suspension of p-chlorophenol, TiO2, and oxigen saturated by the batch system was exposs with UV light, and stirred for a period of time. The concentration of remainder p-chlorophenol was determined by Gas Chromatography. The yields of photodegradation of phenol was calculated by deiermining the amount of the initial and remaining of concentration of p-chlorophenol. In this study, the effict of mass of TiO2 , the initial concentration of p-chlorophenol, and the pH of the solution on the effictiveness of p-chlorophenol photodegradation catalyzed bi TiO2 have been investigated. The effect of the photodegradation process on TiO2 cristally have also studied. The research results showed that the increasing of concentration to mass of TiO2, the initial of concentration of p-chlorophenol, were increased the effect of photodegradation of p-chlorophenol catalyzed by TiO2. It is also found that the effectiveness of p-chlorophenol wasa conciderably influenced by solution pH, regarding the speciation of p-chlorophenol, and TiO2. The highest effectiviness of photodegradation of p'chlorophenol catalyzed by TiO2 was 66.84 % and the condition with giving maximum yields are 20 mg TiO2 in 25 mL solution, 300 mg/L the initial of concentration of p-chlorophenol, the pH of solution 6, and the time contact of about 25 hours. Durin the photodegradation of p-chlorophenol process, TiO2 cristally was partially destroyed as much as 14.13%. Key words: phothodegradation, p-chlorophenol, and TiO2